Reinforcement film
Patent Information
- Application Number
- JP2022036418
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-09
AI Technical Summary
Adhesive films used for reinforcing semiconductor element substrates and flexible devices often cause rainbow-colored unevenness in camera images and have issues with heat resistance, leading to adhesive oozing or air bubble formation during thermocompression bonding.
A reinforcing film with multiple adhesive films, each with specific retardation and storage modulus properties, arranged with gaps to address unevenness and heat resistance requirements, allowing easy attachment to specific parts of the substrate.
The film effectively suppresses rainbow-colored unevenness and ensures excellent heat resistance, preventing adhesive peeling and bubble formation during bonding processes.
Smart Images

Figure 00000042_0000 
Figure 00000042_0001 
Figure 00000042_0002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a reinforcing film. Preferably, the present invention relates to a reinforcing film suitable for optical components. [Background technology]
[0002] Adhesive films, which include a base layer and an adhesive layer, are used to reinforce components of various shapes.
[0003] For example, when bonding integrated circuits (ICs) or flexible printed circuit boards (FPCs) to a semiconductor substrate (e.g., a TFT substrate), thermocompression bonding is usually performed using an anisotropic conductive film (ACF). In some cases, when performing such thermocompression bonding, an adhesive film is pre-applied to the back side of the semiconductor substrate for reinforcement (for example, Patent Document 1).
[0004] Furthermore, in recent years, the manufacturing method for so-called flexible devices such as foldable devices and rollable devices, which are undergoing development, generally involves forming a release layer and a flexible film substrate on a support substrate such as glass, forming a TFT substrate on the film substrate, and then forming an organic EL layer on top of that. The support substrate is then peeled off to manufacture the flexible device, but because the flexible display layer is very thin, malfunctions can occur in the device due to handling. For this reason, an adhesive film is sometimes attached to the back side for reinforcement (for example, Patent Document 2).
[0005] In semiconductor element substrates and flexible devices, cameras are increasingly being mounted at the bottom of the display. In this case, if an adhesive film is attached to the back of the substrate, light transmitted through the adhesive film is captured by the camera. Therefore, depending on the wavelength dependence of the transmittance of the adhesive film, a problem may arise in the camera image where rainbow-colored unevenness occurs. For this reason, the adhesive film attached to the back of the substrate must be designed in a way that does not cause rainbow-colored unevenness.
[0006] Furthermore, if the adhesive film used to bond the back of the circuit board has low heat resistance, problems such as adhesive overflow or air bubbles causing lifting may occur during thermal bonding processes such as IC bonding (reduced bonding resistance).
[0007] As mentioned above, adhesive films used to bond to the back of a circuit board require sufficient suppression of iridescent unevenness and excellent heat resistance, but achieving both of these required characteristics simultaneously is difficult. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Patent No. 5600039 [Patent Document 2] Patent No. 6376271 [Overview of the project] [Problems that the invention aims to solve]
[0009] As a result of repeated studies on the above-mentioned conventional problems, the inventors of the present invention noticed that in semiconductor element substrates and flexible devices, the areas where sufficient suppression of rainbow-color unevenness is required (for example, the area where a camera is mounted at the bottom) and the areas where excellent heat resistance is required (for example, the area where a driving element is mounted) are often different. They then considered that if adhesive films with the required characteristics for each of these areas could be easily attached to their respective locations, the above-mentioned conventional problems could be solved.
[0010] The object of the present invention is to provide a reinforcing film for use in reinforcing a component, which allows for easy bonding of adhesive films with the required characteristics of both parts of the component (where sufficient suppression of iridescent discoloration is required) and parts (where excellent heat resistance is required) to their respective locations. [Means for solving the problem]
[0011] The reinforcing film according to an embodiment of the present invention is a reinforcing film in which two or more adhesive films are arranged with gaps between one release liner and one protective film, each of the two or more adhesive films includes a base material layer and an adhesive layer, the adhesive layers of the two or more adhesive films are directly laminated on the one release liner, the two or more adhesive films include at least one adhesive film (I) and at least one adhesive film (II), the adhesive film (I) has a retardation of 0 nm to 10 nm or 6000 nm or more, when a small piece cut out to a size of 10 mm × 50 mm of the adhesive film (II) is thermocompression bonded at 170° C. for 10 seconds under a load of 2 kg, the lengths of the long sides of the bubble part and the base material deformation part generated are each less than 1.5 mm.
[0012] In one embodiment, the storage modulus at 170° C. of the adhesive layer of the adhesive film (I) is 5.0×10 3 Pa or more and less than 5.0×10 5 Pa.
[0013] In one embodiment, the storage modulus at 170° C. of the adhesive layer of the adhesive film (II) is 5.0×10 3 Pa or more and less than 5.0×10 5 Pa.
[0014] In one embodiment, the area of the adhesive film (I) is larger than the area of the adhesive film (II).
[0015] In one embodiment, the reinforcing film is a reinforcing film for an optical member.
Advantages of the Invention
[0016] According to the present invention, there can be provided a reinforcing film used for reinforcing a member, which can easily bond at respective locations an adhesive film having required characteristics for each of a site where sufficient suppression of iridescent unevenness of the member is required and a site where excellent heat resistance is required.
Brief Description of the Drawings
[0017] [Figure 1] It is a schematic cross-sectional view of a reinforcing film according to one embodiment of the present invention. [Figure 2] It is a schematic plan view of a state in which a release liner is peeled off from one embodiment of the reinforcing film of the present invention. [Figure 3] It is a schematic plan view of a state in which a release liner is peeled off from another embodiment of the reinforcing film of the present invention.
Mode for Carrying Out the Invention
[0018] In this specification, when there is an expression of “(meth)acryl”, it means “acryl and / or methacryl”, when there is an expression of “(meth)acrylate”, it means “acrylate and / or methacrylate”, when there is an expression of “(meth)allyl”, it means “allyl and / or methallyl”, and when there is an expression of “(meth)acrolein”, it means “acrolein and / or methacrolein”. Further, in this specification, when there is an expression of “acid (salt)”, it means “acid and / or its salt”. Examples of the salt include alkali metal salts and alkaline earth metal salts, and specifically, for example, sodium salts, potassium salts and the like can be mentioned.
[0019] ≪≪A. Reinforcing Film≫≫ The reinforcing film according to an embodiment of the present invention is a reinforcing film in which two or more adhesive films are arranged with gaps between one release liner and one protective film, and each of the two or more adhesive films includes a base material layer and an adhesive layer, and the adhesive layer of the two or more adhesive films is directly laminated on the one release liner.
[0020] The number of adhesive films arranged to have a gap between one release liner and one protective film is two or more, preferably 2 to 10, more preferably 2 to 5, even more preferably 2 to 4, and particularly preferably 2 to 3.
[0021] Figure 1 shows a schematic cross-sectional view of one embodiment of the reinforcing film of the present invention. Figure 1 shows an embodiment in which two adhesive films are arranged with a gap between one release liner and one protective film. As shown in Figure 1, the reinforcing film 1000 is arranged between the release liner 100 and the protective film 200 with adhesive films 300a and 300b having a gap L. Adhesive film 300a includes a base layer 10a and an adhesive layer 20a. Adhesive film 300b includes a base layer 10b and an adhesive layer 20b.
[0022] The above-mentioned interval L is preferably 0.1 mm to 5.0 mm, more preferably 0.2 mm to 3.0 mm, even more preferably 0.3 mm to 2.0 mm, particularly preferably 0.5 mm to 1.5 mm, and most preferably 0.7 mm to 1.5 mm.
[0023] The adhesive films can be arranged in any suitable configuration, as long as there is a gap between one release liner and one protective film, without impairing the effects of the present invention. In other words, two or more adhesive films can be arranged with gaps between them, corresponding to the arrangement of each part of the component to be bonded (for example, an optical component) (particularly parts where sufficient suppression of iridescent unevenness is required and parts where excellent heat resistance is required).
[0024] Figure 2 is a schematic plan view of one embodiment of the reinforcing film of the present invention with the release liner removed. Figure 2 shows an embodiment in which two adhesive films are arranged with a gap between them. In Figure 2, adhesive film 300a and adhesive film 300b are arranged on the protective film 200 with a gap L between them.
[0025] Figure 3 is a schematic plan view of another embodiment of the reinforcing film of the present invention, with the release liner removed. Figure 3 shows an embodiment in which three adhesive films are arranged with gaps between them. In Figure 3, adhesive films 300a, 300b, and 300c are arranged on the protective film 200 with gaps L1 and L2 between them.
[0026] The reinforcing film according to the embodiment of the present invention may have any other suitable layer, as long as it does not impair the effects of the present invention. The other layer may be one type or two or more types. Examples of other layers include an antistatic layer, which will be described later.
[0027] At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (I) having a phase difference of 0 nm to 10 nm or 6000 nm or more. Any adhesive film with a phase difference within the above range can be preferably applied to areas where sufficient suppression of iridescent unevenness is required. The method for measuring the above phase difference will be described later.
[0028] A phase difference of 0 nm to 10 nm in the adhesive film (I) means that the adhesive film (I) exhibits a low phase difference, which reduces the change in transmittance for each wavelength and can contribute to sufficient suppression of iridescent unevenness. The above phase difference is preferably 0 nm to 8 nm, more preferably 0 nm to 5 nm, and even more preferably 0 nm to 3 nm.
[0029] A phase difference of 6000 nm or more in the adhesive film (I) means that the adhesive film (I) exhibits an ultra-high phase difference. Although the transmittance changes with each wavelength, the number of peaks in the transmittance spectrum is extremely large and the spacing between these peaks is dense, so rainbow-colored unevenness is no longer visible. The above phase difference is preferably 6500 nm or more, more preferably 7000 nm or more, even more preferably 7500 nm or more, even more preferably 8000 nm or more, even more preferably 8500 nm or more, particularly preferably 9000 nm or more, and most preferably 9200 nm or more. Generally, the larger the upper limit of the phase difference of the adhesive film (I), the better, but considering the balance with other characteristics, it is preferably 15000 nm or less.
[0030] If the phase difference of the adhesive film (I) falls outside the above range, the change in transmittance for each wavelength is large, and because the peak intervals are wide, there is a risk that rainbow-colored unevenness will occur and become visible.
[0031] An adhesive film (I) having a phase difference of 0 nm to 10 nm or 6000 nm or more can be realized, for example, by appropriately selecting the substrate layer (I) and the adhesive layer (I).
[0032] At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (II) in which the length of the long side of the bubble portion and the substrate deformation portion generated when a small piece cut to a size of 10 mm × 50 mm is thermocompression bonded at 170° C. for 10 seconds under a load of 2 kg is less than 1.5 mm each. The length of each of the long sides is preferably less than 1.3 mm, more preferably less than 1.0 mm, still more preferably less than 0.8 mm, and particularly preferably less than 0.5 mm. If the adhesive film has the length of the long side of the bubble portion and the substrate deformation portion within the above range respectively, for example, peeling of the adhesive layer, generation of bubbles, and deformation of the generated bubbles during or after IC bonding can be suppressed. If the length of the long side of the bubble portion and the substrate deformation portion is out of the above range and too large, for example, peeling of the adhesive layer, generation of bubbles, and deformation of the generated bubbles after IC bonding may occur.
[0033] The above-mentioned bubble portion means a void generated between the substrate layer and the adhesive layer, or between the adherend and the adhesive layer. The above-mentioned substrate deformation portion means wrinkles or depressions of the substrate layer deformed by heat. When the size cannot be visually confirmed, the length of these long sides is measured with a microscope. The method for measuring the length of the long side of the bubble portion and the substrate deformation portion will be described later.
[0034] The adhesive film (II) in which the length of the long side of the bubble portion and the substrate deformation portion generated when a small piece cut to a size of 10 mm × 50 mm is thermocompression bonded at 170° C. for 10 seconds under a load of 2 kg is less than 1.5 mm each can be realized, for example, by appropriately selecting the substrate layer (II) and the adhesive layer (II).
[0035] The adhesive layer of the adhesive film (I) preferably has a storage elastic modulus at 170° C. of 5.0×10 3 Pa or more and less than 5.0×10 5 More preferably, it is 7.5×10 3 Pa or more and less than 2.5×10 5 Still more preferably, it is at 1.0×10 4Pa or more 1.0×10 5 It is less than the specified value. If the storage modulus at 170°C is within the specified range, it tends to exhibit excellent adhesion between the substrate layer and the adherend. The method for measuring the storage modulus at 170°C will be described later.
[0036] The adhesive layer of the adhesive film (II) preferably has a storage modulus of 5.0 × 10 at 170°C. 3 Pa or more 5.0×10 5 Less than 7.5 × 10 3 Pa or more 2.5×10 5 Less than 1.0 × 10 4 Pa or more 1.0×10 5 It is less than the specified value. If the storage modulus at 170°C is within the above range, for example, peeling of the adhesive layer during or after IC bonding, the generation of bubbles, and deformation of bubbles that have already formed can be further suppressed. If the storage modulus at 170°C is outside the above range, that is, if it is too high or too low, for example, peeling of the adhesive layer during or after IC bonding, the generation of bubbles, and deformation of bubbles that have already formed may occur. The method for measuring the storage modulus at 170°C will be described later.
[0037] The area of adhesive film (I) (or the total area if there are multiple adhesive films (I)) and the area of adhesive film (II) (or the total area if there are multiple adhesive films (II)) can be appropriately set according to the size of the area where a good effect of suppressing rainbow color unevenness is required and the area where good heat resistance is required. For example, if the area of the area on which the flexible display element is mounted (the area where a good effect of suppressing rainbow color unevenness is required) is larger than the area of the area on which the drive element is mounted (the area where good heat resistance is required), then in such a case, the area of adhesive film (I) (or the total area if there are multiple adhesive films (I)) is preferably larger than the area of adhesive film (II) (or the total area if there are multiple adhesive films (II)).
[0038] In the embodiment of the present invention, the reinforcing film is preferably bonded to the member to be bonded (e.g., an optical member) after peeling off the release liner, and then the protective film is peeled off. Therefore, in order to facilitate the bonding operation, the peeling force (A) of the release liner is preferably smaller than the peeling force (B) of the protective film with respect to a common adhesive film. If the peeling force (A) of the release liner is greater than the peeling force (B) of the protective film with respect to a common adhesive film, there is a risk that delamination will occur between the protective film and the adhesive film when attempting to peel the release liner from the adhesive film.
[0039] The peeling force (A) of the peeling liner is preferably 0 gf / 25 mm to 10 gf / 25 mm, more preferably 0 gf / 25 mm to 8 gf / 25 mm, and even more preferably 0 gf / 25 mm to 5 gf / 25 mm.
[0040] The peel strength (B) of the protective film is preferably 2 gf / 25 mm or more and less than 15 gf / 25 mm, and more preferably 2.5 gf / 25 mm or more and less than 12 gf / 25 mm.
[0041] The reinforcing film according to the embodiment of the present invention can be used in various applications. In terms of being able to more effectively utilize the effects of the present invention, the reinforcing film according to the embodiment of the present invention is typically used as a reinforcing film for optical components. The reinforcing film according to the embodiment of the present invention is particularly suitable for use in devices in which a camera is mounted below the display.
[0042] ≪A-1. Adhesive Film≫ The reinforcing film according to an embodiment of the present invention includes two or more adhesive films. At least one of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention is an adhesive film (I) having a retardation of 0 nm to 10 nm or 6000 nm or more, and at least one is an adhesive film (II) in which the length of the long side of the bubble portion and the substrate deformation portion generated when a small piece cut to a size of 10 mm × 50 mm is thermocompression bonded at 170° C. for 10 seconds under a load of 2 kg is less than 1.5 mm each.
[0043] The adhesive film includes a substrate layer and an adhesive layer. That is, the adhesive film (I) includes a substrate layer (I) and an adhesive layer (I), and the adhesive film (II) includes a substrate layer (II) and an adhesive layer (II).
[0044] In addition to the substrate layer and the adhesive layer, the adhesive film may have any other appropriate layer as long as the effects of the present invention are not impaired. The other layer may be only one type or two or more types. Examples of the other layer include an antistatic layer described later.
[0045] The thicknesses of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention may be the same, or at least one may have a different thickness. From the viewpoint of ease of handling and the like, it is preferable that the thicknesses of the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention are the same.
[0046] <A-1-1. Substrate layer> In this specification, when simply referred to as the "substrate layer", it means including any of the substrate layers included in the two or more adhesive films included in the reinforcing film according to an embodiment of the present invention (that is, including both the substrate layer (I) and the substrate layer (II)).
[0047] The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, even more preferably 10 μm to 100 μm, particularly preferably 15 μm to 90 μm, and most preferably 20 μm to 85 μm. The effects of the present invention can be more fully realized when the thickness of the substrate layer is within the above range.
[0048] Any suitable material can be used as the base layer material, as long as it can exhibit the effects of the present invention as a component of the adhesive film. Typical examples of such base layer materials include resin materials.
[0049] Examples of resin materials used as the base layer material include acrylic resins such as polyimide (PI), polyether ether ketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), as well as polycarbonate, triacetylcellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluororesin, cyclic olefin polymer (COP), and polycarbonate (PC). The resin material used as the base layer material may consist of only one type or two or more types.
[0050] In the reinforcing film according to the embodiment of the present invention, the base material layer (I) contained in the adhesive film (I) and the base material layer (II) contained in the adhesive film (II) may have the same physical properties or may have different physical properties. In the reinforcing film according to the embodiment of the present invention, the base material layer (I) contained in the adhesive film (I) and the base material layer (II) contained in the adhesive film (II) may be made of the same material or may be made of different materials.
[0051] In terms of being able to further exhibit the effects of the present invention, as the resin material for the base material layer (I), it is preferably at least one selected from polyethylene terephthalate (PET), triacetyl cellulose (TAC), and cyclic olefin polymer (COP).
[0052] When an ultra-high retardation film (ultra-birefringent film) is employed as the base material layer (I), the effects of the present invention can be further exhibited. Examples of such a base material layer (I) include, for example, an ultra-high retardation PET film. For the ultra-high retardation, a retardation of 6000 nm or more is a criterion.
[0053] In terms of being able to further exhibit the effects of the present invention, as the resin material for the base material layer (II), it is preferably polyethylene terephthalate (PET).
[0054] <A-1-2. Adhesive layer> In this specification, when simply referred to as the "adhesive layer", it means including any of the adhesive layers included in two or more adhesive films included in the reinforcing film according to the embodiment of the present invention (that is, including both the adhesive layer (I) and the adhesive layer (II)).
[0055] The thickness of the adhesive layer is preferably 1 μm to 250 μm, more preferably 2 μm to 150 μm, still more preferably 3 μm to 100 μm, particularly preferably 5 μm to 50 μm, and most preferably 10 μm to 35 μm. If the thickness of the adhesive layer is within the above range, the effects of the present invention can be more exhibited.
[0056] The adhesive layer is composed of an adhesive. As the adhesive constituting the adhesive layer, an acrylic adhesive is preferred.
[0057] The acrylic adhesive is formed from an acrylic adhesive composition.
[0058] Acrylic adhesives can thus be defined as those formed from acrylic adhesive compositions. This is because acrylic adhesives are formed when acrylic adhesive compositions undergo crosslinking reactions such as heating or ultraviolet irradiation, making it impossible and impractical to directly identify acrylic adhesives by their structure. Therefore, the definition "formed from acrylic adhesive compositions" appropriately identifies acrylic adhesives as a "substance."
[0059] The acrylic adhesive has an adhesive strength to glass of preferably 5 N / 25 mm or more, more preferably 7 N / 25 mm or more, even more preferably 8 N / 25 mm or more, particularly preferably 10 N / 25 mm or more, and most preferably 15 N / 25 mm or more at 23°C, a peeling speed of 300 mm / min, and a peeling angle of 180 degrees. While a higher adhesive strength is generally preferable, considering the balance with other adhesive properties, it is preferably 50 N / 25 mm or less. By adjusting the adhesive strength within the above range, it can function favorably as a reinforcing film. The method for measuring the adhesive strength will be described later.
[0060] As for the method of forming the acrylic adhesive, any suitable method can be employed as long as it does not impair the effects of the present invention. For example, one such method of forming an acrylic adhesive is to apply an acrylic adhesive composition onto any suitable substrate, heat and dry as necessary, and cure as necessary to form the acrylic adhesive in a sheet form on the substrate.
[0061] Any suitable means can be used to apply the acrylic adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0062] The heating and drying of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such heating and drying methods include heating to 60°C to 180°C, or performing an aging treatment at a temperature of approximately room temperature.
[0063] The curing of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. Examples of such curing means include heat, ultraviolet irradiation, laser irradiation, alpha-ray irradiation, beta-ray irradiation, gamma-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0064] Typical methods for forming an acrylic adhesive from an acrylic adhesive composition include: (1) A method for forming a photocurable acrylic adhesive by a photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (typically a partially polymerized acrylic product) prepared by polymerization (typically partial polymerization) using a photopolymerization initiator, (2) A method for forming a thermosetting acrylic adhesive by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer prepared by solution polymerization using a thermal polymerization initiator. These are some examples.
[0065] In other words, typical acrylic adhesives include, (1) A photocurable acrylic adhesive formed by the photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (typically a partially polymerized acrylic product) (P1) prepared by polymerization (typically partial polymerization) using a photopolymerization initiator, (2) A thermosetting acrylic adhesive formed by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer (P2) prepared by solution polymerization using a thermal polymerization initiator. These are some examples.
[0066] [A-1-2-1. Acrylic polymer (P1)] One embodiment of the acrylic polymer is an acrylic polymer (P1) prepared by polymerization (typically partial polymerization) using a photoinitiator. Any suitable method can be used for polymerization using a photoinitiator, such as conventionally known methods, as long as it does not impair the effects of the present invention. Polymerization using a photoinitiator is typically carried out by irradiation with light such as UV.
[0067] The acrylic polymer (P1) is preferably an acrylic partial polymer (sometimes called an acrylic prepolymer). Unlike a complete polymer of the monomer component (preferably a polymer with a polymerization conversion rate of more than 95% by weight), the acrylic partial polymer is a partial polymer obtained by using the monomer component with a polymerization conversion rate of preferably 95% by weight or less.
[0068] The polymerization conversion rate of the acrylic partial polymer is preferably 70% by weight or less, more preferably 60% by weight or less, even more preferably 50% by weight or less, particularly preferably 40% by weight or less, and most preferably 35% by weight or less. The lower limit of the polymerization conversion rate of the acrylic partial polymer is preferably 1% by weight or more, more preferably 5% by weight or more.
[0069] The acrylic polymer (P1) is obtained by polymerizing the monomer component (M1). The monomer component (M1) referred to here does not include the crosslinking agent that may be included in the acrylic adhesive composition, as described later. When obtaining the acrylic polymer (P1) by polymerization, in addition to the monomer component (M1) and the photopolymerization initiator, any suitable additive may be used as long as it does not impair the effects of the present invention.
[0070] Acrylic polymer (P1) can thus be defined as something obtained by polymerizing monomer component (M1). This is because acrylic polymer (P1) is formed when monomer component (M1) undergoes a polymerization reaction, and it is impossible and impractical to directly identify acrylic polymer (P1) by its structure. Therefore, the definition "something obtained by polymerizing monomer component (M1)" appropriately identifies acrylic polymer (P1) as a "substance."
[0071] The acrylic polymer (P1) preferably has a Tg of -70°C to 50°C, more preferably -60°C to 40°C, even more preferably -55°C to 30°C, and particularly preferably -50°C to 20°C, in order to better exhibit the effects of the present invention. By adjusting the Tg of the acrylic polymer (P1) to the above specific range, the effects of the present invention can be better exhibited.
[0072] The Tg of an acrylic polymer (P1) is a value obtained from Fox's formula based on the Tg of the homopolymers of each monomer constituting the acrylic polymer (P1) and the weight fraction (weight-based copolymerization ratio) of the monomers. Fox's formula is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg = Σ(Wi / Tgi)
[0073] In the Fox equation above, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the monomer i homopolymer (unit: K). The Tg of the homopolymer shall be the value specified in the publicly available documents.
[0074] For example, the following values can be used as the Tg of the homopolymer. n-butyl acrylate (BA): -55℃ Lauryl acrylate (LA): -23℃ 2-Ethylhexyl acrylate (2EHA): -70℃ 2-Hydroxyethyl acrylate (2HEA): -15℃ 4-Hydroxybutyl acrylate (4HBA): -40℃ N-vinyl-2-pyrrolidone (NVP): 80℃ Methyl methacrylate (MMA): 105℃
[0075] For homopolymers other than those exemplified above, the values listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) may be used. If multiple values are listed in the "Polymer Handbook," the conventional value shall be adopted. For monomers not listed in the "Polymer Handbook," the catalog values of the monomer manufacturers shall be adopted. For homopolymers of monomers not listed in the "Polymer Handbook" and for which the monomer manufacturers do not provide catalog values, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 shall be used.
[0076] The monomer component (M1) preferably comprises an alkyl (meth)acrylate (a1) and a polar group-containing monomer (b1). The alkyl (meth)acrylate (a1) may consist of only one type or two or more types. The polar group-containing monomer (b1) may consist of only one type or two or more types.
[0077] The alkyl group in the ester portion of alkyl (meth)acrylate (a1) (hereinafter sometimes referred to as "alkyl group in the ester portion") does not include alkyl groups containing hydroxyl groups or alkyl groups containing polar groups other than hydroxyl groups. Therefore, alkyl (meth)acrylate (a1) is clearly distinguished from polar group-containing monomer (b1).
[0078] The content of alkyl (meth)acrylate (a1) in the monomer component (M1) is preferably 40% to 99% by weight, more preferably 45% to 90% by weight, even more preferably 50% to 80% by weight, and particularly preferably 60% to 75% by weight, in order to better exhibit the effects of the present invention.
[0079] The alkyl group of the ester portion is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 18 carbon atoms, even more preferably an alkyl group having 2 to 16 carbon atoms, particularly preferably an alkyl group having 3 to 14 carbon atoms, and most preferably an alkyl group having 6 to 14 carbon atoms, in order to better express the effects of the present invention.
[0080] The alkyl group in the ester portion is preferably a linear alkyl group, as this allows for better expression of the effects of the present invention. Here, "linear" includes both linear and branched alkyl groups.
[0081] Examples of alkyl(meth)acrylates (a1) in which the alkyl group of the ester portion is a chain alkyl group having 1 to 20 carbon atoms include methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate, and Examples include sooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0082] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -10°C or lower, more preferably -12°C or lower, even more preferably -15°C or lower, particularly preferably -18°C or lower, and most preferably -20°C or lower. The lower limit of the above glass transition temperature Tg is preferably -80°C or higher. The glass transition temperature Tg of the homopolymer (homopolymer) of the alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) may affect the adhesive properties of the acrylic polymer (P1). By using an alkyl (meth)acrylate (a1) as the alkyl (meth)acrylate (a1) that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range, the effects of the present invention can be better expressed.
[0083] Here, the glass transition temperature (Tg) of the homopolymer (a1) of the alkyl (meth)acrylate that may be contained in the monomer component (M1) can be a value described in publicly available documents. For example, the value described in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. If multiple values are described in the "Polymer Handbook," the conventional value should be adopted. For alkyl (meth)acrylates not described in the "Polymer Handbook," the catalog value from the monomer manufacturer should be adopted. For alkyl (meth)acrylate homopolymers that are not described in the "Polymer Handbook" and for which the monomer manufacturer does not provide a catalog value, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 should be used.
[0084] In order to further enhance the effects of the present invention, the alkyl (meth)acrylate (a1) that may be included in the monomer component (M1) preferably includes alkyl (meth)acrylate (a1-1) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C). By including alkyl (meth)acrylate (a1-1) in alkyl (meth)acrylate (M1), the effects of the present invention can be further enhanced.
[0085] Examples of alkyl (meth)acrylate (a1-1) include lauryl acrylate (LA) (whose homopolymer has a glass transition temperature Tg = -23°C).
[0086] The content of alkyl(meth)acrylate (a1-1) in the total amount of alkyl(meth)acrylate (a1-1) that can be contained in the monomer component (M1) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 20% to 70% by weight, and particularly preferably 30% to 60% by weight, in order to better express the effects of the present invention.
[0087] The content of alkyl (meth)acrylate (a1-1) in the total amount of monomer component (M1) is preferably 0% to 70% by weight, more preferably 10% to 60% by weight, even more preferably 20% to 50% by weight, and particularly preferably 30% to 45% by weight, in order to better express the effects of the present invention.
[0088] In order to further enhance the effects of the present invention, the alkyl (meth)acrylate (a1) that may be included in the monomer component (M1) preferably includes alkyl (meth)acrylate (a1-2) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C). By including alkyl (meth)acrylate (a1-2) in alkyl (meth)acrylate (M1), the effects of the present invention can be further enhanced.
[0089] Examples of alkyl (meth)acrylates (a1-2) include 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg = -70°C of its homopolymer).
[0090] The content ratio of alkyl (meth)acrylate (a1-2) in the total amount of alkyl (meth)acrylate (a1) that can be contained in the monomer component (M1) is preferably 20% to 90% by weight, more preferably 30% to 80% by weight, even more preferably 40% to 70% by weight, and particularly preferably 50% to 65% by weight, in order to better express the effects of the present invention.
[0091] The content of alkyl (meth)acrylate (a1-2) in the total amount of monomer component (M1) is preferably 10% to 100% by weight, more preferably 20% to 90% by weight, even more preferably 30% to 80% by weight, and particularly preferably 40% to 70% by weight, in order to better exhibit the effects of the present invention.
[0092] The content of the polar group-containing monomer (b1) in the monomer component (M1) is preferably 1% to 50% by weight, more preferably 1% to 40% by weight, even more preferably 1% to 30% by weight, and particularly preferably 1% to 20% by weight, in order to better express the effects of the present invention.
[0093] In order to better express the effects of the present invention, the polar group-containing monomer (b1) preferably comprises at least one selected from the group consisting of a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2), and more preferably comprises both a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2).
[0094] The hydroxyl group-containing monomer (b1-1) may be one type or two or more types.
[0095] Examples of hydroxyl group-containing monomers (b1-1) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide.
[0096] In order to better express the effects of the present invention, the hydroxyl group-containing monomer (b1-1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -60°C to -10°C, more preferably -55°C to -10°C, and even more preferably -45°C to -10°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (b1-1) can affect the adhesive properties of the acrylic polymer (P1). By using a hydroxyl group-containing monomer (b1-1) that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer component (M1), the effects of the present invention can be better expressed.
[0097] The glass transition temperature Tg of homopolymers of hydroxyl group-containing monomers (b1-1) can be determined by referring to the explanation for the glass transition temperature Tg of alkyl (meth)acrylates (a1).
[0098] In order to further express the effects of the present invention, the hydroxyl group-containing monomer (b1-1) is preferably a hydroxyalkyl (meth)acrylate, more preferably a hydroxyalkyl (meth)acrylate in which the alkyl group portion of the hydroxyalkyl group is a linear alkyl group having 2 to 4 carbon atoms, even more preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer) and 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer), and particularly preferably 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer).
[0099] The content of hydroxyl group-containing monomer (b1-1) in polar group-containing monomer (b1) is preferably 10% to 100% by weight, more preferably 20% to 90% by weight, even more preferably 30% to 85% by weight, and particularly preferably 40% to 80% by weight, in order to better exhibit the effects of the present invention.
[0100] The content of the hydroxyl group-containing monomer (b1-1) in the monomer component (M1) is preferably 0% to 80% by weight, more preferably 10% to 70% by weight, even more preferably 20% to 60% by weight, and particularly preferably 30% to 50% by weight, in order to better express the effects of the present invention.
[0101] The monomers (b1-2) having polar groups other than hydroxyl groups may be one type or two or more types.
[0102] Examples of monomers having polar groups other than hydroxyl groups (b1-2) include N-vinyl-2-pyrrolidone, nitrogen-containing monomers other than N-vinyl-2-pyrrolidone, carboxyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, acid anhydride group-containing monomers, vinyl esters (e.g., vinyl acetate (VAc), vinyl propionate, vinyl laurate), aromatic vinyl compounds, amide group-containing monomers, epoxy group-containing monomers, (meth)acryloylmorpholine, and vinyl ethers.
[0103] Examples of monomers containing a carboxyl group include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0104] Examples of nitrogen-containing monomers other than N-vinyl-2-pyrrolidone include methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinyl carboxylic acid amides, and N-vinylcaprolactam; as well as cyano group-containing acrylic monomers such as acrylonitrile and methacrylonitrile.
[0105] In order to better express the effects of the present invention, the monomer (b1-2) having polar groups other than hydroxyl groups preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -30°C to 100°C, more preferably -20°C to 95°C, and even more preferably -10°C to 90°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the monomer (b1-2) having polar groups other than hydroxyl groups may affect the adhesive properties of the acrylic polymer (P1). By using a monomer (b1-2) having polar groups other than hydroxyl groups that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer (b1-2) that can be included in the monomer component (M1), the effects of the present invention can be better expressed.
[0106] As monomers having polar groups other than hydroxyl groups (b1-2), those that can better express the effects of the present invention are preferably monomers having polar groups other than hydroxyl groups whose homopolymers have a glass transition temperature Tg of 50°C to 100°C. The glass transition temperature Tg of the homopolymer of this monomer is preferably 60°C to 95°C, and more preferably 70°C to 90°C.
[0107] For the glass transition temperature Tg of homopolymers of monomers (b1-2) having polar groups other than hydroxyl groups, the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0108] In order to further enhance the effects of the present invention, preferred monomers (b1-2) having polar groups other than hydroxyl groups include N-vinyl-2-pyrrolidone (the glass transition temperature Tg=80°C of its homopolymer).
[0109] The content of monomers (b1-2) having polar groups other than hydroxyl groups in the polar group-containing monomer (b1) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 15% to 70% by weight, and particularly preferably 20% to 60% by weight, in order to better express the effects of the present invention.
[0110] The content of monomers (b1-2) having polar groups other than hydroxyl groups in monomer component (M1) is preferably 0% to 20% by weight, more preferably 0% to 10% by weight, even more preferably 0% to 9% by weight, and particularly preferably 0% to 8% by weight, in order to better express the effects of the present invention.
[0111] To further enhance the effects of the present invention, the monomer component (M1) preferably comprises an alkyl (meth)acrylate (a1) and at least one selected from the group consisting of a hydroxyl group-containing monomer (b1-1) and a monomer having a polar group other than a hydroxyl group (b1-2), more preferably comprising an alkyl (meth)acrylate (a1), a hydroxyl group-containing monomer (b1-1), and a monomer having a polar group other than a hydroxyl group (b1-2), and even more preferably a homopolymer thereof. The material comprises an alkyl (meth)acrylate (a1-1) having a glass transition temperature Tg in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C), an alkyl (meth)acrylate (a1-2) whose homopolymer has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), a hydroxyl group-containing monomer (b1-1), and a monomer (b1-2) having a polar group other than a hydroxyl group.
[0112] In order to further express the effects of the present invention, the total content ratio of alkyl (meth)acrylate (a1-1) in the monomer component (M1) having a glass transition temperature Tg of its homopolymer in the range of -40°C to -10°C (preferably -35°C to -15°C, more preferably -30°C to -20°C), alkyl (meth)acrylate (a1-2) having a glass transition temperature Tg of its homopolymer in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), hydroxyl group-containing monomer (b1-1), and monomer (b1-2) having polar groups other than hydroxyl groups is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, particularly preferably 90% to 100% by weight, and most preferably 95% to 100% by weight.
[0113] In order to further enhance the effects of the present invention, the monomer component (M1) preferably includes lauryl acrylate, 2-ethylhexyl acrylate, 4-hydroxybutyl acrylate, and N-vinyl-2-pyrrolidone.
[0114] The monomer component (M1) may include other monomers (c1) that do not fall under either alkyl (meth)acrylate (a1) or polar group-containing monomer (b1). The other monomers (c1) can be used, for example, to adjust the glass transition temperature (Tg) or tackiness of the acrylic polymer (P1). The other monomers may be one type or two or more types.
[0115] The content of other monomers (c1) in monomer component (M1) is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less.
[0116] The photopolymerization initiator can be appropriately selected from any suitable photopolymerization initiator depending on the type of polymerization method. There may be only one type of photopolymerization initiator, or two or more types.
[0117] Examples of photopolymerization initiators include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators.
[0118] Examples of benzoin ether-based photopolymerization initiators include, for example, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one (a commercially available product is, for example, trade name "OMNIRAD651," manufactured by IGM Resins BV), and anisole methyl ether.
[0119] Examples of acetophenone-based photopolymerization initiators include, for example, 1-hydroxycyclohexylphenyl ketone (commercially available, for example, trade name "OMNIRAD184," manufactured by IGM Resins BV), 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (commercially available, for example, trade name "OMNIRAD2959," manufactured by IGM Resins BV), 2-hydroxy-2-methyl-1-phenyl-propan-1-one, and methoxyacetophenone.
[0120] Examples of α-ketol-based photopolymerization initiators include, for example, 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)-phenyl]-2-hydroxy-2-methylpropan-1-one.
[0121] Examples of aromatic sulfonyl chloride-based photopolymerization initiators include, for example, 2-naphthalenesulfonyl chloride.
[0122] Examples of photoactive oxime-based photopolymerization initiators include, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime.
[0123] Examples of benzoin-based photopolymerization initiators include, for instance, benzoin.
[0124] Examples of benzyl-based photopolymerization initiators include, for example, benzyl.
[0125] Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenyl ketone.
[0126] Examples of ketal-based photopolymerization initiators include, for example, benzyldimethyl ketal.
[0127] Examples of thioxanthone-based photopolymerization initiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0128] Examples of acylphosphine-based photopolymerization initiators include, specifically, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)(2,4,4-trimethylpentyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-n-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)-(2-methylpropan-1-yl)phosphine oxide, bis(2,6-dimethoxybenzoyl)-(1-methylpropan-1-yl)phosphine oxide, and bis(2,6-dimethyl (Xybenzoyl)-t-butylphosphine oxide, bis(2,6-dimethoxybenzoyl)cyclohexylphosphine oxide, bis(2,6-dimethoxybenzoyl)octylphosphine oxide, bis(2-methoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2-methoxybenzoyl)(1-methylpropan-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,6-diethoxybenzoyl)(1-methylprop Pan-1-yl)phosphine oxide, bis(2,6-dibutoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,4-dimethoxybenzoyl)(2-methylpropan-1-yl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)(2,4-dipentoxyphenyl)phosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2 - Phenylethylphosphine oxide, bis(2,6-dimethoxybenzoyl)benzylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylpropylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2-phenylethylphosphine oxide, 2,6-dimethoxybenzoylbenzylbutylphosphine oxide, 2,6-dimethoxybenzoylbenzyloctylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diisopropylphenylphosphine oxide, bis(2,4,6-Trimethylbenzoyl)-2-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-4-methylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,5-diethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,3,5,6-tetramethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl) Examples include -2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)isobutylphosphine oxide, 2,6-dimethitoxybenzoyl-2,4,6-trimethylbenzoyl-n-butylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-dibutoxyphenylphosphine oxide, 1,10-bis[bis(2,4,6-trimethylbenzoyl)phosphine oxide]decane, and tri(2-methylbenzoyl)phosphine oxide.
[0129] The amount of photopolymerization initiator used can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of photopolymerization initiator used is preferably 0.001 to 10 parts by weight, more preferably 0.005 to 5 parts by weight, even more preferably 0.007 to 3 parts by weight, and particularly preferably 0.01 to 1 part by weight, per 100 parts by weight of monomer component (M1), in order to better express the effects of the present invention.
[0130] [A-1-2-2. Acrylic polymer (P2)] One embodiment of the acrylic polymer is an acrylic polymer (P2) prepared by solution polymerization using a thermal polymerization initiator. As for the polymerization method using the thermal polymerization initiator, any suitable method can be used, such as conventionally known methods, as long as it does not impair the effects of the present invention.
[0131] The acrylic polymer (P2) is obtained by polymerizing the monomer component (M2). The monomer component (M2) referred to here does not include the crosslinking agent that may be included in the acrylic adhesive composition, as described later. When obtaining the acrylic polymer (P2) by polymerization, in addition to the monomer component (M2) and the thermal polymerization initiator, any suitable additive may be used as long as it does not impair the effects of the present invention.
[0132] Acrylic polymers (P2) can thus be defined as those obtained by polymerizing monomer components (M2). This is because acrylic polymers (P2) are formed when monomer components (M2) undergo a polymerization reaction, and it is impossible and impractical to directly identify acrylic polymers (P2) by their structure. Therefore, the definition "obtained by polymerizing monomer components (M2)" appropriately identifies acrylic polymers (P2) as a "substance."
[0133] The acrylic polymer (P2) preferably has a Tg of -70°C to 50°C, more preferably -60°C to 40°C, even more preferably -55°C to 30°C, and particularly preferably -50°C to 20°C, in order to better exhibit the effects of the present invention. By adjusting the Tg of the acrylic polymer (P2) to the above specific range, the effects of the present invention can be better exhibited.
[0134] The Tg of an acrylic polymer (P2) refers to the value obtained from Fox's formula, based on the Tg of the homopolymer of each monomer constituting the acrylic polymer (P2) and the weight fraction (weight-based copolymerization ratio) of said monomer. For Fox's formula and the Tg of various homopolymers, refer to the explanation in section [A-1-2-1. Acrylic Polymer (P1)].
[0135] The monomer component (M2) preferably comprises an alkyl (meth)acrylate (a2) and a polar group-containing monomer (b2). The alkyl (meth)acrylate (a2) may consist of only one type or two or more types. The polar group-containing monomer (b2) may consist of only one type or two or more types.
[0136] The alkyl group in the ester portion of alkyl(meth)acrylate (a2) (hereinafter sometimes referred to as "alkyl group in the ester portion") does not include alkyl groups containing hydroxyl groups or alkyl groups containing polar groups other than hydroxyl groups. Therefore, alkyl(meth)acrylate (a2) is clearly distinguished from polar group-containing monomer (b2).
[0137] The content of alkyl (meth)acrylate (a2) in the monomer component (M2) is preferably 40% to 99% by weight, more preferably 45% to 90% by weight, even more preferably 50% to 80% by weight, and particularly preferably 60% to 75% by weight, in order to better express the effects of the present invention.
[0138] The alkyl group of the ester portion is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 18 carbon atoms, even more preferably an alkyl group having 1 to 16 carbon atoms, and particularly preferably an alkyl group having 1 to 14 carbon atoms, in order to better express the effects of the present invention.
[0139] The alkyl group in the ester portion is preferably a linear alkyl group, as this allows for better expression of the effects of the present invention. Here, "linear" includes both linear and branched alkyl groups.
[0140] For alkyl(meth)acrylates (a2) in which the alkyl group of the ester portion is a chain-like alkyl group having 1 to 20 carbon atoms, the explanation for alkyl(meth)acrylates (a1) in which the alkyl group of the ester portion is a chain-like alkyl group having 1 to 20 carbon atoms in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0141] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a2) that may be included in the monomer component (M2) preferably includes alkyl (meth)acrylate (a2-1) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C). The effects of the present invention can be better expressed by including alkyl (meth)acrylate (a2-1) in alkyl (meth)acrylate (M2).
[0142] Examples of alkyl (meth)acrylate (a2-1) include 2-ethylhexyl acrylate (2EHA) (the glass transition temperature Tg = -70°C of its homopolymer).
[0143] The content ratio of alkyl (meth)acrylate (a2-1) in the total amount of alkyl (meth)acrylate (a2) that can be contained in the monomer component (M2) is preferably 30% to 100% by weight, more preferably 40% to 100% by weight, even more preferably 50% to 100% by weight, and particularly preferably 60% to 100% by weight, in order to better exhibit the effects of the present invention.
[0144] The content of alkyl (meth)acrylate (a2-1) in the total amount of monomer component (M2) is preferably 50% to 100% by weight, more preferably 60% to 100% by weight, even more preferably 70% to 100% by weight, and particularly preferably 80% to 100% by weight, in order to better exhibit the effects of the present invention.
[0145] In order to better express the effects of the present invention, the alkyl (meth)acrylate (a2) that may be included in the monomer component (M2) preferably includes alkyl (meth)acrylate (a2-2) whose homopolymer (homopolymer) has a glass transition temperature Tg in the range of 90°C to 120°C (preferably 95°C to 115°C, more preferably 100°C to 110°C). The effects of the present invention can be better expressed by including alkyl (meth)acrylate (a2-2) in alkyl (meth)acrylate (M2).
[0146] Examples of alkyl (meth)acrylate (a2-2) include methyl methacrylate (MMA) (whose homopolymer has a glass transition temperature Tg = 105°C).
[0147] The content ratio of alkyl (meth)acrylate (a2-2) in the total amount of alkyl (meth)acrylate (a2) that can be contained in the monomer component (M2) is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, and particularly preferably 90% to 100% by weight, in order to better exhibit the effects of the present invention.
[0148] The content of alkyl (meth)acrylate (a2-2) in the total amount of monomer component (M2) is preferably 0% to 40% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 20% by weight, and particularly preferably 0% to 15% by weight, in order to better express the effects of the present invention.
[0149] The content of the polar group-containing monomer (b2) in the monomer component (M2) is preferably 0% to 45% by weight, more preferably 0% to 40% by weight, even more preferably 0% to 35% by weight, and particularly preferably 0% to 30% by weight, in order to better express the effects of the present invention.
[0150] In order to better express the effects of the present invention, the polar group-containing monomer (b2) preferably comprises at least one selected from the group consisting of a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2), and more preferably comprises both a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2).
[0151] The hydroxyl group-containing monomer (b2-1) may be one type or two or more types.
[0152] For hydroxyl group-containing monomers (b2-1), the explanation for hydroxyl group-containing monomers (b1-1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0153] In order to better express the effects of the present invention, the hydroxyl group-containing monomer (b2-1) preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -60°C to -10°C, more preferably -55°C to -10°C, and even more preferably -45°C to -10°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the hydroxyl group-containing monomer (b2-1) can affect the adhesive properties of the acrylic polymer (P2). By using a hydroxyl group-containing monomer (b2-1) that can be included in the monomer component (M2) and whose homopolymer (homopolymer) has a glass transition temperature Tg within the above range, the effects of the present invention can be better expressed.
[0154] For the glass transition temperature Tg of homopolymers of hydroxyl group-containing monomers (b2-1), the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0155] In order to further express the effects of the present invention, the hydroxyl group-containing monomer (b2-1) is preferably a hydroxyalkyl (meth)acrylate, more preferably a hydroxyalkyl (meth)acrylate in which the alkyl group portion of the hydroxyalkyl group is a linear alkyl group having 2 to 4 carbon atoms, even more preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer) and 4-hydroxybutyl acrylate (4HBA) (glass transition temperature Tg = -40°C of its homopolymer), and particularly preferably 2-hydroxyethyl acrylate (HEA) (glass transition temperature Tg = -15°C of its homopolymer).
[0156] The content ratio of hydroxyl group-containing monomer (b2-1) in polar group-containing monomer (b2) is preferably 10% to 100% by weight, more preferably 20% to 100% by weight, even more preferably 30% to 100% by weight, and particularly preferably 40% to 100% by weight, in order to better exhibit the effects of the present invention.
[0157] The content of the hydroxyl group-containing monomer (b2-1) in the monomer component (M2) is preferably 0% to 45% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 25% by weight, and particularly preferably 0% to 20% by weight, in order to better express the effects of the present invention.
[0158] The monomer (b2-2) having a polar group other than a hydroxyl group may be one type or two or more types.
[0159] For monomers having polar groups other than hydroxyl groups (b2-2), the explanation for monomers having polar groups other than hydroxyl groups (b1-2) in section [A-1-2-1. Acrylic polymers (P1)] may be applied.
[0160] In order to better express the effects of the present invention, the monomer (b2-2) having polar groups other than hydroxyl groups preferably has a glass transition temperature Tg of its homopolymer (homopolymer) of -30°C to 100°C, more preferably -20°C to 95°C, and even more preferably -10°C to 90°C. The glass transition temperature Tg of the homopolymer (homopolymer) of the monomer (b2-2) having polar groups other than hydroxyl groups may affect the adhesive properties of the acrylic polymer (P2). By using a monomer (b2-2) having polar groups other than hydroxyl groups that has a glass transition temperature Tg of its homopolymer (homopolymer) within the above range as the monomer (b2-2) that can be included in the monomer component (M2), the effects of the present invention can be better expressed.
[0161] As monomers having polar groups other than hydroxyl groups (b2-2), those that can better express the effects of the present invention are preferably monomers having polar groups other than hydroxyl groups whose homopolymer has a glass transition temperature Tg of 50°C to 100°C. The glass transition temperature Tg of the homopolymer of this monomer is preferably 60°C to 95°C, and more preferably 70°C to 90°C.
[0162] For the glass transition temperature Tg of homopolymers of monomers (b2-2) having polar groups other than hydroxyl groups, the explanation for the glass transition temperature Tg of homopolymers of alkyl (meth)acrylates (a1) that may be contained in the monomer component (M1) in section [A-1-2-1. Acrylic polymers (P1)] can be applied.
[0163] In order to further enhance the effects of the present invention, a preferred monomer (b2-2) having a polar group other than a hydroxyl group is N-vinyl-2-pyrrolidone (the glass transition temperature Tg = 80°C of its homopolymer).
[0164] The content of monomers (b2-2) having polar groups other than hydroxyl groups in the polar group-containing monomer (b2) is preferably 0% to 90% by weight, more preferably 10% to 80% by weight, even more preferably 20% to 70% by weight, and particularly preferably 30% to 60% by weight, in order to better express the effects of the present invention.
[0165] The content of monomers (b2-2) having polar groups other than hydroxyl groups in monomer component (M2) is preferably 0% to 35% by weight, more preferably 0% to 30% by weight, even more preferably 0% to 25% by weight, and particularly preferably 0% to 20% by weight, in order to better express the effects of the present invention.
[0166] To further enhance the effects of the present invention, the monomer component (M2) preferably comprises an alkyl (meth)acrylate (a2) and at least one selected from the group consisting of a hydroxyl group-containing monomer (b2-1) and a monomer having a polar group other than a hydroxyl group (b2-2), more preferably comprising an alkyl (meth)acrylate (a2), a hydroxyl group-containing monomer (b2-1), and a monomer having a polar group other than a hydroxyl group (b2-2), and even more preferably a glass homopolymer thereof. The material comprises an alkyl (meth)acrylate (a2-1) having a transition temperature Tg in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), an alkyl (meth)acrylate (a2-2) whose homopolymer has a glass transition temperature Tg in the range of -120°C to -90°C (preferably -115°C to -95°C, more preferably -110°C to -100°C), a hydroxyl group-containing monomer (b2-1), and a monomer having a polar group other than a hydroxyl group (b2-2).
[0167] In order to further express the effects of the present invention, the total content ratio of alkyl (meth)acrylate (a2-1) in the monomer component (M2) having a glass transition temperature Tg of its homopolymer in the range of -80°C to -60°C (preferably -75°C to -60°C, more preferably -75°C to -65°C), alkyl (meth)acrylate (a2-2) having a glass transition temperature Tg of its homopolymer in the range of -120°C to -90°C (preferably -115°C to -95°C, more preferably -110°C to -100°C), hydroxyl group-containing monomer (b2-1), and monomer (b2-2) having polar groups other than hydroxyl groups is preferably 60% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 80% to 100% by weight, particularly preferably 90% to 100% by weight, and most preferably 95% to 100% by weight.
[0168] In order to further enhance the effects of the present invention, the monomer component (M1) preferably includes 2-ethylhexyl acrylate, methyl methacrylate, 2-hydroxyethyl acrylate, and N-vinyl-2-pyrrolidone.
[0169] The monomer component (M2) may include other monomers (c2) that do not fall under either alkyl (meth)acrylate (a2) or polar group-containing monomers (b2). The other monomers (c2) can be used, for example, to adjust the glass transition temperature (Tg) of the acrylic polymer (P1), adjust the tackiness, etc. The other monomers may be one type or two or more types.
[0170] The content of other monomers (c2) in monomer component (M1) is preferably 20% by weight or less, more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less.
[0171] The thermal polymerization initiator can be appropriately selected from any suitable thermal polymerization initiator depending on the type of polymerization method. There may be only one thermal polymerization initiator or two or more.
[0172] Examples of thermal polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid)dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, and 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]di Azo initiators such as hydrochlorides, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(N,N'-dimethylene isobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate, di(2-ethylhexyl) peroxydicarbonate, di Examples include peroxide initiators such as (4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butylperoxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butylhydroperoxide, and hydrogen peroxide; redox initiators combining peroxides with reducing agents, such as combinations of persulfates and sodium bisulfite, or combinations of peroxides and sodium ascorbate; substituted ethane initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds.
[0173] The amount of thermal polymerization initiator used can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of thermal polymerization initiator used is preferably 0.001 to 10 parts by weight, more preferably 0.005 to 5 parts by weight, even more preferably 0.007 to 3 parts by weight, and particularly preferably 0.01 to 1 part by weight, per 100 parts by weight of monomer component (M2), in order to better express the effects of the present invention.
[0174] [A-1-2-3. First embodiment of acrylic adhesive (photocurable acrylic adhesive)] The first embodiment of the acrylic adhesive is a photocurable acrylic adhesive, which is typically formed by a photocuring reaction of a photocurable acrylic adhesive composition containing an acrylic polymer (P1).
[0175] The photocurable acrylic adhesive is formed from a photocurable acrylic adhesive composition by any suitable method. Typical such formation methods include applying the photocurable acrylic adhesive composition onto any suitable substrate, then placing another suitable substrate on the surface of the applied adhesive layer, and curing it by ultraviolet irradiation. Any suitable application method can be used for applying the photocurable acrylic adhesive composition, as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0176] Heating may be performed as needed during the formation of the photocurable acrylic adhesive. Furthermore, aging may be performed for purposes such as adjusting component migration within the formed photocurable acrylic adhesive, promoting the crosslinking reaction, and alleviating any strain that may exist within the photocurable acrylic adhesive.
[0177] The photocurable acrylic adhesive composition may contain alkyl (meth)acrylate (a1-2). The type of alkyl (meth)acrylate (a1-2) may be the same as or different from the type of alkyl (meth)acrylate (a1-2) that can be used to produce the acrylic polymer (P1).
[0178] The content of alkyl (meth)acrylate (a1-2) in the photocurable acrylic adhesive composition is preferably 20% to 90% by weight, more preferably 30% to 80% by weight, even more preferably 40% to 70% by weight, and particularly preferably 50% to 65% by weight, relative to the total amount (100% by weight) of the acrylic polymer (P1), in order to better exhibit the effects of the present invention.
[0179] The photocurable acrylic adhesive composition preferably contains a crosslinking agent (L1). The crosslinking agent (L1) may be one type or two or more types.
[0180] The amount of crosslinking agent (L1) in the photocurable acrylic adhesive composition can be set to any appropriate amount as long as it does not impair the effects of the present invention. The amount of crosslinking agent (L1) in the photocurable acrylic adhesive composition is preferably 0.001 to 0.5 parts by weight, more preferably 0.005 to 0.3 parts by weight, even more preferably 0.01 to 0.2 parts by weight, and particularly preferably 0.05 to 0.1 parts by weight, per 100 parts by weight of acrylic polymer (P1), in order to better express the effects of the present invention.
[0181] As the crosslinking agent (L1), any suitable crosslinking agent can be used as long as it does not impair the effects of the present invention. Preferably, such a crosslinking agent (L1) is a polyfunctional (meth)acrylate.
[0182] As the polyfunctional (meth)acrylate, any suitable polyfunctional (meth)acrylate can be used as long as it does not impair the effects of the present invention. There may be only one type of polyfunctional (meth)acrylate, or there may be two or more types. Specifically, such polyfunctional (meth)acrylates include, for example, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6- Examples include ester compounds of polyhydric alcohols such as hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate with (meth)acrylic acid; allyl(meth)acrylate; vinyl(meth)acrylate; divinylbenzene; epoxy acrylate; polyester acrylate; urethane acrylate; butyl di(meth)acrylate; and hexyl di(meth)acrylate.
[0183] The light-curing acrylic adhesive composition may contain an acrylic oligomer. The acrylic oligomer may be one type or two or more types.
[0184] The content of acrylic oligomers in the photocurable acrylic adhesive composition can be set to any appropriate content as long as it does not impair the effects of the present invention. The content of acrylic oligomers in the photocurable acrylic adhesive composition is preferably 0.1 to 20 parts by weight, more preferably 1 to 15 parts by weight, even more preferably 3 to 10 parts by weight, and particularly preferably 5 to 8 parts by weight, per 100 parts by weight of acrylic polymer (P1), in order to better express the effects of the present invention.
[0185] The weight-average molecular weight of the acrylic oligomer is preferably 1,000 to 30,000, more preferably 1,000 to 20,000, even more preferably 1,500 to 10,000, and particularly preferably 2,000 to 8,000. The effects of the present invention can be more fully realized when the photocurable acrylic adhesive composition contains an acrylic oligomer.
[0186] The weight-average molecular weight (Mw) can be determined by converting it to polystyrene equivalent using the GPC method. For example, it can be measured using the high-speed GPC instrument "HPLC-8120GPC" manufactured by Tosoh Corporation under the following conditions. Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000 Solvent: tetrahydrofuran Flow rate: 0.6ml / min
[0187] The glass transition temperature (Tg) of the acrylic oligomer is preferably 20°C to 300°C, more preferably 30°C to 300°C, and more preferably 40°C to 300°C.
[0188] The Tg of an acrylic oligomer refers to the value obtained from Fox's formula, based on the Tg of the homopolymer of each monomer constituting the acrylic oligomer and the weight fraction (weight-based copolymerization ratio) of the monomer. For Fox's formula and the Tg of various homopolymers, refer to the explanation in section [A-1-2-1. Acrylic Polymers (P1)].
[0189] As acrylic oligomers, those obtained from monomer compositions containing a (meth)acrylic acid ester having a cyclic structure within the molecule are preferred, and those obtained from monomer compositions containing a (meth)acrylic acid alkyl ester having a cyclic structure within the molecule and a linear or branched alkyl group are more preferred.
[0190] The (meth)acrylic acid ester having a cyclic structure within the molecule may be one type or two or more types.
[0191] The alkyl (meth)acrylate having a linear or branched alkyl group may be one type or two or more types.
[0192] In (meth)acrylic acid esters having a cyclic structure within the molecule, the cyclic structure may be either an aromatic ring or a non-aromatic ring.
[0193] Examples of aromatic rings include aromatic carbon rings (such as monocyclic carbon rings like benzene rings, and fused carbon rings like naphthalene rings), and various aromatic heterocycles.
[0194] Examples of non-aromatic rings include non-aromatic aliphatic rings (non-aromatic alicyclic rings) (e.g., cycloalkane rings such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane rings; cycloalkene rings such as cyclohexene rings), non-aromatic bridged rings (e.g., bicyclic hydrocarbon rings in pinane, pinene, bornane, norbornane, norbornene; aliphatic hydrocarbon rings with three or more rings (bridged hydrocarbon rings) in adamantane, etc.), and non-aromatic heterocycles (e.g., epoxy rings, oxolane rings, oxetane rings). Examples of aliphatic hydrocarbon rings with three or more rings (bridged hydrocarbon rings with three or more rings) include dicyclopentanyl group, dicyclopentenyl group, adamantyl group, tricyclopentanyl group, and tricyclopentenyl group.
[0195] Examples of (meth)acrylic acid esters having a cyclic structure within the molecule include, for example, cycloalkyl (meth)acrylic acid esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1- Examples include (meth)acrylic acid esters having three or more aliphatic hydrocarbon rings, such as adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate; and (meth)acrylic acid esters having aromatic rings, such as aryl (meth)acrylates like phenyl (meth)acrylate, aryloxyalkyl (meth)acrylates like phenoxyethyl (meth)acrylate, and arylalkyl (meth)acrylates like benzyl (meth)acrylate.
[0196] As (meth)acrylic acid esters having a cyclic structure within the molecule, non-aromatic ring-containing (meth)acrylic acid esters are preferred in terms of being able to better express the effects of the present invention, more preferably cyclohexyl acrylate (CHA), cyclohexyl methacrylate (CHMA), dicyclopentanyl acrylate (DCPA), and dicyclopentanyl methacrylate (DCPMA), and even more preferably dicyclopentanyl acrylate (DCPA) and dicyclopentanyl methacrylate (DCPMA).
[0197] The content of (meth)acrylic acid esters having a cyclic structure within the molecule in all monomers that can be used to constitute the acrylic oligomer is preferably 10 to 90 parts by weight, and more preferably 20 to 80 parts by weight, per 100 parts by weight of all monomers, in order to better express the effects of the present invention.
[0198] Examples of alkyl (meth)acrylate esters having linear or branched alkyl groups include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and methacrylic acid Examples include alkyl esters of (meth)acrylates having 1 to 20 carbon atoms in the alkyl group, such as isooctyl, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, methyl methacrylate (MMA) is preferred in that it can better exhibit the effects of the present invention.
[0199] The content of alkyl (meth)acrylate having a linear or branched alkyl group in the total monomers that can be used to constitute the acrylic oligomer is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight, per 100 parts by weight of the total monomer, in order to better express the effects of the present invention.
[0200] The total monomers (monomer composition) that can be used to constitute the acrylic oligomer may include, in addition to (meth)acrylic acid esters having a cyclic structure in the molecule and (meth)acrylic acid alkyl esters having linear or branched alkyl groups, other monomers (copolymerizable monomers) that can copolymerize with these monomers. The content of other monomers (copolymerizable monomers) in the total monomers (monomer composition) that can be used to constitute the acrylic oligomer is preferably less than 50 parts by weight, more preferably 40 parts by weight or less, even more preferably 30 parts by weight or less, and particularly preferably 20 parts by weight or less, per 100 parts by weight of the total monomer.
[0201] Other monomers (copolymerizable monomers) include, for example, alkoxyalkyl esters of (meth)acrylates (e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.), carboxyl group-containing monomers (e.g., acid anhydride group-containing monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, maleic anhydride, etc.), hydroxyl group-containing monomers (e.g., hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc.); vinyl alcohol; allyl alcohol; etc. Examples include monomers containing amide groups (e.g., (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, etc.), monomers containing amino groups (e.g., aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, t-butylaminoethyl(meth)acrylate, etc.), monomers containing cyano groups (e.g., acrylonitrile, methacrylonitrile, etc.), monomers containing sulfonic acid groups (e.g., sodium vinylsulfonate, etc.), monomers containing phosphate groups (e.g., 2-hydroxyethylacryloylphosphate, etc.), monomers containing isocyanate groups (e.g., 2-methacryloyloxyethyl isocyanate, etc.), and monomers containing imide groups (e.g., cyclohexylmaleimide, isopropylmaleimide, etc.).
[0202] The total monomers (monomer composition) that can be used to constitute the acrylic oligomer particularly preferably include (1) at least one monomer selected from dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and (2) methyl methacrylate. In this case, the content of monomer (1) is preferably 30 to 70 parts by weight and the content of monomer (2) is preferably 30 to 70 parts by weight per 100 parts by weight of the total monomers (monomer composition) that can be used to constitute the acrylic oligomer.
[0203] Acrylic oligomers can be produced by any suitable polymerization method, provided that the effects of the present invention are not impaired. Examples of such polymerization methods include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by active energy ray irradiation (active energy ray polymerization). Among these, bulk polymerization and solution polymerization are preferred, and solution polymerization is more preferred.
[0204] Examples of solvents that can be used in polymerization include organic solvents such as esters like ethyl acetate and n-butyl acetate; aromatic hydrocarbons like toluene and benzene; aliphatic hydrocarbons like n-hexane and n-heptane; alicyclic hydrocarbons like cyclohexane and methylcyclohexane; and ketones like methyl ethyl ketone and methyl isobutyl ketone. One solvent may be used, or two or more solvents may be used.
[0205] In polymerization, any suitable polymerization initiator (e.g., a thermal polymerization initiator or a photopolymerization initiator) can be used, as long as it does not impair the effects of the present invention. One polymerization initiator may be used, or two or more may be used. When performing solution polymerization, it is preferable to use an oil-soluble polymerization initiator.
[0206] As a thermal polymerization initiator, any suitable thermal polymerization initiator can be used as long as it does not impair the effects of the present invention. There may be only one thermal polymerization initiator or two or more. For specific examples of such thermal polymerization initiators, refer to the explanation of thermal polymerization initiators in section [A-1-2-2. Acrylic Polymers (P2)].
[0207] The content of the thermal polymerization initiator is preferably 0.1 to 15 parts by weight per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0208] As the photopolymerization initiator, any suitable photopolymerization initiator can be used as long as it does not impair the effects of the present invention. There may be only one type of photopolymerization initiator or two or more types. For specific examples of such photopolymerization initiators, refer to the explanation of photopolymerization initiators in section [A-1-2-1. Acrylic Polymers (P1)].
[0209] The photopolymerization initiator content is preferably 0.001 to 0.5 parts by weight per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0210] In polymerization of acrylic oligomers, a chain transfer agent may be used to adjust the molecular weight (preferably to adjust the weight-average molecular weight to 1,000 to 30,000). Examples of chain transfer agents include 2-mercaptoethanol, α-thioglycerol, 2,3-dimercapto-1-propanol, octyl mercaptan, t-nonyl mercaptan, dodecyl mercaptan (lauryl mercaptan), t-dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, t-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, thioglycolic acid ester of ethylene glycol, thioglycolic acid ester of neopentyl glycol, thioglycolic acid ester of pentaerythritol, and α-methylstyrene dimer. Among these, α-thioglycerol and methyl thioglycolate are preferred, and α-thioglycerol is particularly preferred, from the viewpoint of suppressing whitening of the double-sided adhesive tape of the present invention. The chain transfer agent may be one type or two or more types.
[0211] The content of the chain transfer agent is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and even more preferably 0.3 to 10 parts by weight, per 100 parts by weight of the total monomer (monomer composition) that can be used to constitute the acrylic oligomer.
[0212] The photocurable acrylic adhesive composition may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include tackifiers, inorganic fillers, organic fillers, metal powders, pigments, colorants, foils, softeners, anti-aging agents, conductive agents, UV absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, other crosslinking agents, solvents, catalysts, crosslinking catalysts, and crosslinking retarders.
[0213] [A-1-2-4. Second embodiment of acrylic adhesive (thermosetting acrylic adhesive)] A second embodiment of the acrylic adhesive is a thermosetting acrylic adhesive, which is typically formed by a crosslinking reaction of a thermosetting acrylic adhesive composition containing an acrylic polymer (P2).
[0214] The thermosetting acrylic adhesive is formed from a thermosetting acrylic adhesive composition by any suitable method. Typical such formation methods include applying the thermosetting acrylic adhesive composition onto any suitable substrate, heating and drying as necessary, and curing as necessary to form a sheet of thermosetting acrylic adhesive on the substrate. Any application method can be used as long as it does not impair the effects of the present invention. Examples of such application methods include the roll coating method, gravure roll coating method, reverse roll coating method, kiss roll coating method, dip roll coating method, bar coating method, roll brush coating method, spray coating method, knife coating method, air knife coating method, comma coating method, direct coating method, and die coating method.
[0215] The heating and drying of the thermosetting acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. For example, heating to a temperature of about 60°C to 180°C is one such heating and drying method. The curing of the acrylic adhesive composition can be carried out by any suitable means, as long as it does not impair the effects of the present invention. For example, curing methods include ultraviolet irradiation, laser irradiation, alpha-ray irradiation, beta-ray irradiation, gamma-ray irradiation, X-ray irradiation, and electron beam irradiation.
[0216] When forming a thermosetting acrylic adhesive, aging may be performed as needed to adjust component migration within the formed thermosetting acrylic adhesive, promote crosslinking reactions, and alleviate any strain that may exist within the photocurable acrylic adhesive.
[0217] The thermosetting acrylic adhesive composition preferably contains a crosslinking agent (L2). The crosslinking agent (L2) may be one type or two or more types.
[0218] The use of a crosslinking agent (L2) can impart appropriate cohesive force to a thermosetting acrylic adhesive. The crosslinking agent (L2) can be included in the thermosetting acrylic adhesive in the form after the crosslinking reaction, in the form before the crosslinking reaction, in a partially crosslinked form, or in intermediate or composite forms therein. Typically, the crosslinking agent (L2) is included in the thermosetting acrylic adhesive in the form after the crosslinking reaction.
[0219] The proportion of the crosslinking agent (L2) in the thermosetting acrylic adhesive composition is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, even more preferably 0.01 to 3 parts by weight, even more preferably 0.01 to 2 parts by weight, particularly preferably 0.01 to 1.5 parts by weight, and most preferably 0.01 to 1.3 parts by weight, per 100 parts by weight of the acrylic polymer (P2), in order to better express the effects of the present invention.
[0220] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxides. In terms of being able to better express the effects of the present invention, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and peroxides are preferred, and isocyanate-based crosslinking agents and peroxides are more preferred.
[0221] Isocyanate-based crosslinking agents can be compounds having two or more isocyanate groups (including isocyanate-regenerating polar groups in which isocyanate groups are temporarily protected by a blocking agent or quantification, etc.) in one molecule. Examples of isocyanate-based crosslinking agents include aromatic isocyanates such as tolylene diisocyanate and xylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.
[0222] Examples of isocyanate-based crosslinking agents include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / tolylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: Coronate HL), and isocyanurate derivatives of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, Examples include isocyanate adducts such as Coronate HX; trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D110N), trimethylolpropane adducts of xylylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D120N), trimethylolpropane adducts of isophorone diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D140N), trimethylolpropane adducts of hexamethylene diisocyanate (e.g., Mitsui Chemicals, product name: Takenate D160N); polyether polyisocyanates, polyester polyisocyanates, and adducts thereof with various polyols; and polyfunctionalized polyisocyanates with isocyanurate bonds, biuret bonds, allophanate bonds, etc. Among these, aromatic isocyanates and alicyclic isocyanates are preferred because they can achieve a good balance between deformability and cohesiveness.
[0223] As epoxy crosslinking agents, polyfunctional epoxy compounds having two or more epoxy groups in one molecule can be used. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylenediline, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitol polyglycidyl ether. Examples of epoxy crosslinking agents include tel, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate ester, diglycidyl o-phthalate ester, triglycidyl-tris(2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of commercially available epoxy crosslinking agents include the trade names "Tetrad C" and "Tetrad X" manufactured by Mitsubishi Gas Chemical Company.
[0224] Examples of peroxides include dibenzoyl peroxide, dicumyl peroxide, di-t-butyl peroxide, di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butyl hydroperoxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexine-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-mono(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, and t-butylperoxy Examples include neodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexyl peroxy)cyclohexane, 1,1-di(t-butyl peroxy)cyclohexane, t-butyl peroxy-2-ethylhexyl carbonate, t-amyl peroxyisopropyl carbonate, 3,5,5-trimethylhexanoyl peroxide, t-butyl peroxy-2-hexanoate, t-butyl peroxypivalate, and t-hexyl peroxypivalate. Examples of commercially available peroxides include the "Nipper BMT" series and "Nipper BW" series manufactured by Nippon Oil & Fats Co., Ltd.
[0225] The thermosetting acrylic adhesive composition may contain an acrylic oligomer. The acrylic oligomer may be one type or two or more types. The description of the acrylic oligomer can be found in section [A-1-2-3. First Embodiment of Acrylic Adhesive (Photocuring Acrylic Adhesive)].
[0226] The thermosetting acrylic adhesive composition may contain any suitable other components as long as the effects of the present invention are not impaired. Examples of such other components include tackifiers, inorganic fillers, organic fillers, metal powders, pigments, colorants, foil-like materials, softeners, anti-aging agents, conductive agents, ultraviolet absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, other crosslinking agents, solvents, catalysts, crosslinking catalysts, and crosslinking retardants.
[0227] <A-1-3. Antistatic Layer> In addition to the base material layer and the adhesive layer, the adhesive film may have an antistatic layer. The antistatic layer can be provided, for example, on the side opposite to the adhesive layer of the base material layer, between the base material layer and the adhesive layer, or on the side opposite to the base material layer of the adhesive layer.
[0228] As the thickness of the antistatic layer, any appropriate thickness can be adopted as long as the effects of the present invention are not impaired. Such a thickness is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm, still more preferably 7.5 nm to 800 nm, and particularly preferably 10 nm to 700 nm.
[0229] The antistatic layer may be only one layer or two or more layers.
[0230] As the antistatic layer, any appropriate antistatic layer can be adopted as long as it can exhibit an antistatic effect and the effects of the present invention are not impaired. Such an antistatic layer is preferably an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on any appropriate base material layer. Specifically, for example, it is an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on a resin base film. Specific coating methods include roll coating method, bar coating method, gravure coating method, etc. [[ID=********]] [[ID=********]]
[0231] [[ID=********]] As the conductive polymer, any suitable conductive polymer can be used as long as it does not impair the effects of the present invention. Examples of such conductive polymers include conductive polymers doped with polyanions in a π-conjugated conductive polymer. Examples of π-conjugated conductive polymers include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of polyanions include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl sulfonic acid, and polymethacrylic acid. There may be only one conductive polymer or two or more conductive polymers.
[0232] ≪A-2. Peel-off Liner≫ The thickness of the release liner is preferably 1 μm to 300 μm, more preferably 10 μm to 200 μm, even more preferably 20 μm to 150 μm, particularly preferably 35 μm to 100 μm, and most preferably 50 μm to 80 μm, in order to better exhibit the effects of the present invention.
[0233] The release liner typically includes a resin-based film.
[0234] Examples of resin-based films include: plastic films made from polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); plastic films made from olefin resins with α-olefins as monomer components, such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); plastic films made from polyvinyl chloride (PVC); plastic films made from vinyl acetate resins; plastic films made from polycarbonate (PC); and polyphenylene sulfide (PPS). Examples include: plastic films composed of: polyamide (nylon), all-aromatic polyamide (aramid), and other amide resins; plastic films composed of polyimide resins; plastic films composed of polyetheretherketone (PEEK); plastic films composed of olefin resins such as polyethylene (PE) and polypropylene (PP); and plastic films composed of fluorine resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer.
[0235] The resin substrate film may consist of only one layer or two or more layers. The resin substrate film may also be stretched.
[0236] The resin substrate film may be surface-treated. Examples of surface treatments include corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high-voltage electric shock exposure, ionizing radiation treatment, and coating with an undercoat.
[0237] The resin substrate film may contain any suitable additives, as long as they do not impair the effects of the present invention.
[0238] The release liner may have a release layer. When the release liner has a release layer, typically the side with the release layer is directly laminated onto the adhesive layer of the adhesive film.
[0239] The material used to form the release layer can be any suitable material, as long as it does not impair the effects of the present invention. Examples of such materials include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and fatty acid amide-based release agents. Among these, silicone-based release agents are preferred. The release layer can be formed as a coating layer.
[0240] The thickness of the release layer can be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. Such a thickness is preferably 10 nm to 2000 nm, more preferably 10 nm to 1500 nm, even more preferably 10 nm to 1000 nm, and particularly preferably 10 nm to 500 nm.
[0241] The release layer may consist of only one layer or two or more layers.
[0242] Examples of silicone-based release layers include addition-reaction type silicone resins. Specifically, examples of addition-reaction type silicone resins include KS-774, KS-775, KS-778, KS-779H, KS-847H, and KS-847T from Shin-Etsu Chemical Co., Ltd.; TPR-6700, TPR-6710, and TPR-6721 from Toshiba Silicone Co., Ltd.; and SD7220 and SD7226 from Toray Dow Corning Co., Ltd. The amount of silicone-based release layer applied (after drying) is preferably 0.01 g / m². 2 ~2g / m 2 More preferably 0.01 g / m 2 ~1g / m 2 And more preferably 0.01 g / m 2 ~0.5g / m 2 That is the case.
[0243] The release layer can be formed, for example, by applying the above-described forming material onto any suitable layer by a conventionally known coating method such as reverse gravure coating, bar coating, die coating, etc., and then usually curing it by heat treatment at about 120 to 200°C. Further, heat treatment and irradiation with active energy rays such as ultraviolet irradiation may be used in combination as necessary.
[0244] The release liner may have an antistatic layer.
[0245] Regarding the antistatic layer, the description in the section <A-1-3. Antistatic layer> can be incorporated.
[0246] One embodiment of the release liner includes a resin base film and a release layer in this order. Typically, this embodiment consists of a resin base film and a release layer.
[0247] Another embodiment of the release liner includes a resin base film, an antistatic layer, and a release layer in this order. Typically, this embodiment consists of a resin base film, an antistatic layer, and a release layer.
[0248] Yet another embodiment of the release liner includes an antistatic layer, a resin base film, an antistatic layer, and a release layer in this order. Typically, this embodiment consists of an antistatic layer, a resin base film, an antistatic layer, and a release layer.
[0249] ≪A-3. Protective film≫ As the protective film, any suitable protective film can be adopted as long as the effects of the present invention are not impaired. Such a protective film is typically a protective film having an adhesive layer on at least one side of a base film, and a protective film known as an optical surface protective film can preferably be adopted.
[0250] On the surface of the adhesive layer of the protective film, a release liner may be provided as necessary. Regarding the release liner, the description in the section ≪A-2. Release liner≫ can be incorporated.
[0251] The thickness of the base film is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, even more preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm. The effects of the present invention can be more fully realized when the thickness of the base film is within the above range.
[0252] The thickness of the adhesive layer is preferably 1 μm to 250 μm, more preferably 2 μm to 150 μm, even more preferably 3 μm to 100 μm, particularly preferably 5 μm to 50 μm, and most preferably 7 μm to 30 μm. The effects of the present invention can be more fully realized when the thickness of the adhesive layer is within the above range.
[0253] Preferably, the base film and adhesive layer are those that can be used in protective films known as optical surface protective films, and for example, the description of the base film and adhesive layer in Japanese Patent Application Publication No. 2018-109092 can be used as reference.
[0254] <<<B. Manufacturing of reinforcing film>>> The reinforcing film according to the embodiment of the present invention can be manufactured by any suitable method, as long as the effects of the present invention are not impaired.
[0255] As a representative example of a method for manufacturing a reinforcing film according to an embodiment of the present invention, we will describe a case in which the reinforcing film according to an embodiment of the present invention has a release liner, two adhesive films, and a protective film in this order, and the two adhesive films, adhesive film (I) and adhesive film (II), are arranged with a gap between them.
[0256] One embodiment of the method for manufacturing a reinforcing film according to an embodiment of the present invention involves manufacturing a laminate (X) having two adhesive films on one release liner and a protective film, and then attaching the substrate layer side of the laminate (X) to one of the protective films and the adhesive layer side of the protective film.
[0257] The laminate (X) can be manufactured by, for example, applying an adhesive composition (typically an acrylic adhesive composition) that forms the adhesive that constitutes the adhesive layer of the adhesive film onto a substrate layer, heating and drying as necessary, and curing as necessary to form the adhesive layer on the substrate layer. A release liner (or the side with a release layer, if present) can be attached to the side of the adhesive layers (I) and (II) of the two adhesive films (I) and (II) obtained in this way that is opposite to the substrate layers (I) and (II), so that the two adhesive films (I) and (II) are arranged with a gap between them.
[0258] The protective film is manufactured, for example, by applying an adhesive composition that forms the adhesive that constitutes the adhesive layer onto a base film, heating and drying as necessary, and curing as necessary to form the adhesive layer on the base film.
[0259] Until the laminate (X) and the protective film are bonded together, any suitable release liner may be applied to protect the exposed surface of the adhesive layer of the protective film.
[0260] <<<C. Uses of Reinforcement Film>>> The reinforcing film according to the embodiment of the present invention can be used in any suitable application. The reinforcing film according to the embodiment of the present invention is preferably used, for example, to reinforce optical components and electronic components. Examples of optical components include LCDs, touch panels using LCDs, color filters used in LCDs, polarizing plates, and the like.
[0261] The optical and electronic components described above may be flexible devices such as bendable devices, foldable devices, or rollable devices, each having a movable bending portion. Furthermore, the optical and electronic components may be devices in which a camera is mounted at the bottom of the display. [Examples]
[0262] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The test and evaluation methods in the examples are as follows. When "parts" is written, it means "parts by weight" unless otherwise specified, and when "%" is written, it means "percent by weight" unless otherwise specified.
[0263] <Measuring Phase Difference> The adhesive film with a release liner that was prepared was cut to TD50mm x MD50mm. The release liner was peeled off the cut adhesive film with the release liner, and the front phase difference (R0) was measured by setting it in the measuring device. The measuring device was configured as follows depending on the substrate used. COP film: AxoScan (manufactured by Axometrics) High Retardation PET Film: AxoScan (manufactured by Axometrics) PET film: AxoScan (manufactured by Axometrics) TAC Film: KOBRA-WPR (manufactured by Oji Measuring Instruments Co., Ltd.)
[0264] <Heat resistance (bonding resistance)> The release liner was peeled off the adhesive film with the prepared release liner, attached to a polyimide film (UBE Industries, UPILEX50S), and heat-pressed at 50°C and 0.5 MPa for 15 minutes. The sample was then cut to TD10mm x MD50mm. The cut sample was placed on a hot plate at 170°C, and a glass slide (Matsunami Glass, S1112) and a 2kg weight were placed on top of it. The sample was then heat-pressed for 10 seconds. The sample was set so that all surfaces of the substrate were in contact with the hot plate. After 10 seconds of heat pressing, the sample was removed, and the longest side of the air bubbles and substrate deformation areas was measured using a microscope (OLYMPUS, BX51TRF) (magnification: 5x).
[0265] <Measurement of Storage Modulus G'> The storage elastic modulus G’ corresponds to the portion stored as elastic energy when the material is deformed and is an index representing the degree of hardness. Only the adhesive layer of the adhesive film was taken out, laminated to a thickness of about 1 mm, punched into a φ8 mm size, and cylindrical pellets were produced as measurement samples. Using a dynamic viscoelasticity measuring device (manufactured by TA Instruments, DHR), the obtained measurement sample was fixed to a fixture of φ8 mm parallel plates, and the storage elastic modulus G’ was calculated. The measurement conditions are as follows. Measurement: Shear mode Temperature range: -60°C to 200°C Temperature rising rate: 5°C / min Frequency: 1 Hz
[0266] <Measurement of adhesion to glass> The produced adhesive film with a release liner was cut into TD25 mm × MD100 mm. The release liner was peeled off from the cut adhesive film with a release liner and pasted onto glass (manufactured by Matsunami Glass, S2004U8) with a 2 kg roller in one round trip. The obtained evaluation sample was stored at room temperature for 30 minutes and then measured with a tensile testing machine. As the tensile testing machine, the product named “Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus)” manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile testing machine, the tensile test was started. The conditions of the tensile test were a peeling angle of 180 degrees and a peeling speed (tensile speed) of 300 mm / min. The load when peeling the adhesive film from the above glass was measured, and the average load at that time was taken as the adhesive force.
[0267] <Measurement of peel force (A) of the release liner> The produced adhesive film with a release liner was cut into TD50 mm × MD100 mm to obtain samples. Double-sided tape No. 31B (manufactured by Nitto Denko Corporation) was pasted on glass, and the sample obtained by laminating the base material layer surface of the obtained sample and the glass was used as an evaluation sample, and the peel force of the release liner was measured with a tensile tester. As the tensile tester, the product named "Autograph AG-Xplus HS 6000 mm / min High-speed Model (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile tester, the tensile test was started. The conditions of the tensile test were a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load at the time of peeling the release liner from the adhesive film was measured, and the average load at that time was defined as the peel force (A) of the release liner. The numerical values described in the table are the values converted to the measured values per 25 mm width.
[0268] <Measurement of the peel force (B) of the protective film> The produced protective film was cut into TD25 mm × MD100 mm. The release liner was peeled off from the produced adhesive film with a release liner and pasted on glass (manufactured by Matsunami Glass, S2004U8). The release liner of the above protective film was peeled off and pasted on the base material layer surface of the adhesive film with a 2 kg roller for one round to obtain an evaluation sample. After storing at room temperature for 30 minutes, the peel force of the protective film was measured with a tensile tester. As the tensile tester, the product named "Autograph AG-Xplus HS 6000 mm / min High-speed Model (AG-50NX plus)" manufactured by Shimadzu Corporation was used. After setting the evaluation sample in the tensile tester, the tensile test was started. The conditions of the tensile test were a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load at the time of peeling the protective film from the adhesive film was measured, and the average load at that time was defined as the peel force (B) of the protective film.
[0269] [Production Example 1]: Production of the adhesive layer (1) <Production of the acrylic adhesive composition (1)> 63 parts by weight of 2-ethylhexyl acrylate (2EHA), 15 parts by weight of N-vinyl-2-pyrrolidone (NVP), 9 parts by weight of methyl methacrylate (MMA), 13 parts by weight of 2-hydroxyethyl acrylate (HEA), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 133 parts by weight of ethyl acetate as a polymerization solvent were placed in a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature was raised to 65°C and the reaction was carried out for 5 hours, then the temperature was raised to 70°C and the reaction was carried out for 2 hours, and ethyl acetate was added to obtain a solution of acrylic polymer (1) with a solid content of 30% by weight. The weight-average molecular weight of acrylic polymer (1) was 800,000. Next, an isocyanate crosslinking agent (product name "Takenate D110N", manufactured by Mitsui Chemicals, Inc.) was added to a solution of acrylic polymer (1) in an amount equivalent to 1.1 parts by weight in terms of solid content per 100 parts by weight of acrylic polymer (1) (solid content), and this was mixed to produce an acrylic adhesive composition (1). <Manufacturing of adhesive layer (1)> A 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRV50T100J") with a silicone-based release layer on its surface was used as a release liner (1a) (double-layer release film), and the above-mentioned acrylic adhesive composition (1) was applied to the release liner (1a) to a thickness of 13 μm to form a coating layer. Next, the release liner (1a) with the coating layer formed was placed in an oven and dried at 130°C for 1 minute. Then, a 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") with a silicone-based release layer on its surface was used as a release liner (1b) to protect the surface of the coating layer, and a 13 μm thick adhesive layer (1) was manufactured as a laminate (1) of release liner (1a) / adhesive layer (1) / release liner (1b). The properties of the adhesive layer (1) are shown in Table 1.
[0270] [Manufacturing Example 2]: Manufacturing of the adhesive layer (2) <Prepolymer composition (2) production> A prepolymer composition (2) (polymerization rate: approximately 10%) was obtained by blending 60 parts by weight of lauryl acrylate (LA), 22 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), 10 parts by weight of N-vinyl-2-pyrrolidone (NVP) as monomer components for prepolymer formation, and 0.01 parts by weight of BASF's "Irgacure 184" and 0.01 parts by weight of BASF's "Irgacure 651" as photopolymerization initiators, and polymerization was carried out by irradiation with ultraviolet light. <Manufacturing of acrylic oligomers> 60 parts by weight of dicyclopentanyl methacrylate (DCPMA) and 40 parts by weight of methyl methacrylate (MMA) as monomer components, 3.4 parts by weight of α-thioglycerol as a chain transfer agent, and ethyl acetate as a polymerization solvent were mixed to a concentration of 60% and stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) was added as a thermal polymerization initiator and the mixture was reacted at 70°C for 2 hours. Subsequently, 0.1 parts of AIBN were added, and the temperature was raised to 80°C and the mixture was reacted for 2 hours to obtain an acrylic oligomer solution. Next, the acrylic oligomer solution was dried at 85°C to obtain an acrylic oligomer powder. The weight-average molecular weight of the acrylic oligomer was 5100, and the glass transition temperature (Tg) was 130°C. <Manufacturing of acrylic adhesive composition (2)> To 100 parts by weight of the above prepolymer composition (2), 37 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.08 parts by weight of 1,6-hexanediol diacrylate (HDDA), 6 parts by weight of the above acrylic oligomer, and 0.3 parts by weight of a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM403") were added as post-addition components, and these were then uniformly mixed to produce acrylic adhesive composition (2). <Manufacturing of adhesive layer (2)> A 75 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "Diafol MRF75") with a silicone-based release layer on its surface was used as a release liner (2a) (also serving as a heavy-duty release film), and the above-mentioned acrylic adhesive composition (2) was applied to the release liner (2a) to a thickness of 15 μm to form a coating layer. On the formed coating layer, a 75 μm thick PET film (Mitsubishi Chemical's "Diafol MRE75") with one side treated with silicone release treatment was laminated as a cover sheet (also serving as a light-release film) as a release liner (2b). The resulting laminate was subjected to an irradiation intensity of 5 mW / cm² at the irradiation surface directly beneath the lamp, from the cover sheet side. 2 Using a black light positioned to achieve this, ultraviolet light was irradiated to perform photocuring, and a 15 μm thick adhesive layer (2) was manufactured as a laminate (2) of a release liner (2a) / adhesive layer (2) / release liner (2b). The properties of the adhesive layer (2) are shown in Table 1.
[0271] [Table 1]
[0272] [Manufacturing Example 3] (Manufacturing of adhesive film (1)) As a binder, 100 parts by weight of a 25% aqueous solution of polyester resin (Toyobo Co., Ltd., trade name "Byronal MD-1480"), 20 parts by weight of a conductive polymer, and 5 parts by weight of a melamine-based crosslinking agent (Sumitomo Chemical Co., Ltd., trade name "Sumimar M-50W") were added to a mixed solvent of water / ethanol (1 / 1 by weight ratio) and stirred for about 20 minutes to mix thoroughly. In this way, a coating material (X) with a solid content of approximately 0.4% was prepared. As the conductive polymer, an aqueous solution containing 0.5% poly(3,4-ethylenedioxythiophene) (PEDOT) and 0.8% polystyrene sulfonate (weight-average molecular weight 150,000) (PSS) (Bytron P, HCStark) was used. A high retardation PET substrate (Toyobo Co., Ltd.'s "SRF TA053") with a thickness of 80 μm was coated with the above coating material (X) using a bar coater, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Manufacturing Example 1 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (1) with a release liner (1a).
[0273] [Manufacturing Example 4] (Manufacturing of adhesive film (2)) A high retardation PET substrate (Toyobo Co., Ltd.'s "SRF TA053") with a thickness of 80 μm was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Manufacturing Example 2 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (2) with a release liner (2a).
[0274] [Manufacturing Example 5] (Manufacturing of adhesive film (3)) A cycloolefin (COP) substrate (ZF-14, manufactured by Nippon Zeon Co., Ltd.) with a thickness of 50 μm was coated with the coating material (X) prepared in Production Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. On the surface of the antistatic layer - attached substrate opposite to the antistatic layer, the adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Production Example 1 was bonded using a hand roller, and heat - pressed at 50 °C and 0.5 MPa for 15 minutes to obtain an adhesive film (3) with a release liner (1a).
[0275] [Production Example 6] (Production of Adhesive Film (4)) On one side of a cycloolefin (COP) substrate (「ZF - 14」manufactured by Nippon Zeon Co., Ltd.) with a thickness of 50 μm as the substrate layer, the coating material (X) prepared in Production Example 3 was applied using a bar coater, and heated at 130 °C for 2 minutes to dry, thereby producing an antistatic layer - attached substrate having a transparent antistatic layer with a thickness of 40 nm on one side of the substrate. On the surface of the antistatic layer - attached substrate opposite to the antistatic layer, the adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Production Example 2 was bonded using a hand roller, and heat - pressed at 50 °C and 0.5 MPa for 15 minutes to obtain an adhesive film (4) with a release liner (2a).
[0276] [Production Example 7] (Production of Adhesive Film (5))<00009�8>On one side of a triacetyl cellulose (TAC) substrate (「ZRD40SL(ZRG)」manufactured by Fuji Film Co., Ltd.) with a thickness of 40 μm as the substrate layer, the coating material (X) prepared in Production Example 3 was applied using a bar coater, and heated at 130 °C for 2 minutes to dry, thereby producing an antistatic layer - attached substrate having a transparent antistatic layer with a thickness of 40 nm on one side of the substrate. On the surface of the antistatic layer - attached substrate opposite to the antistatic layer, the adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Production Example 1 was bonded using a hand roller, and heat - pressed at 50 °C and 0.5 MPa for 15 minutes to obtain an adhesive film (5) with a release liner (1a).
[0277] [Production Example 8] (Production of Adhesive Film (6)) A 40 μm thick triacetylcellulose (TAC) substrate (Fujifilm Corporation's "ZRD40SL (ZRG)") was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and then heated at 130°C for 2 minutes to dry, thereby producing a substrate with an antistatic layer having a 40 nm thick transparent antistatic layer on one side of the substrate. An adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Manufacturing Example 2 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and the two layers were heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (6) with a release liner (2a).
[0278] [Manufacturing Example 9] (Manufacturing of adhesive film (7)) A polyethylene terephthalate (PET) substrate (T100-75S, manufactured by Mitsubishi Chemical Corporation) with a thickness of 75 μm (hereinafter sometimes referred to as PET75) was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (1) obtained by peeling off the release liner (1b) from the laminate (1) obtained in Manufacturing Example 1 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (7) with a release liner (1a).
[0279] [Manufacturing Example 10] (Manufacturing of adhesive film (8)) A polyethylene terephthalate (PET) substrate (T100-75S, manufactured by Mitsubishi Chemical Corporation) with a thickness of 75 μm (hereinafter sometimes referred to as PET75) was coated with the coating material (X) prepared in Manufacturing Example 3 using a bar coater on one side, and dried by heating at 130°C for 2 minutes to produce a substrate with an antistatic layer having a transparent antistatic layer with a thickness of 40 nm on one side. An adhesive layer (2) obtained by peeling off the release liner (2b) from the laminate (2) obtained in Manufacturing Example 2 was attached to the side of the fabricated antistatic layer substrate opposite to the antistatic layer using a hand roller, and heated and pressed at 50°C and 0.5 MPa for 15 minutes to obtain an adhesive film (8) with a release liner (2a).
[0280] [Manufacturing Example 11] (Manufacturing of protective films) 100 parts by weight of 2-ethylhexyl acrylate (2EHA) and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) as monomer components, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 182 parts by weight of ethyl acetate as a polymerization solvent were placed in a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature was raised to 60°C and the reaction was carried out for 4.5 hours, and then the temperature was raised to 70°C and the reaction was carried out for another 4.5 hours to obtain a solution of acrylic polymer with a solid content of 35.5% by weight. The weight-average molecular weight of the acrylic polymer was 800,000. To 100 parts by weight of the obtained acrylic polymer, 0.03 parts by weight of a tin catalyst (Envirizer OL-1, manufactured by Tokyo Fine Chemical Co., Ltd.), 5 parts by weight of an isocyanate crosslinking agent (Coronate HX, manufactured by Nippon Polyurethane Industries Co., Ltd.), 0.3 parts by weight of a surfactant (Aqualon HS-10, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), toluene as a solvent, and acetylacetone as a crosslinking retarder were mixed to a solution concentration of 20% to prepare an adhesive solution. Acetylacetone was added in an amount of 5 parts by weight relative to the amount of solvent. The obtained adhesive solution was coated onto a 50 μm thick PET film (Mitsubishi Chemical's "T100C50"), dried at 130°C for 1 minute, and then a 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") was laminated as a release liner to create a protective film. The thickness of the adhesive layer was 10 μm.
[0281] [Example 1] A 50 μm thick polyethylene terephthalate (PET) film (Mitsubishi Chemical's "MRQ50T100J") (150 mm x 70 mm in size) was used as a release liner. On this film, two adhesive films were used: adhesive film (I), cut to a size of 134 mm x 70 mm (2); and adhesive film (II), cut to a size of 15 mm x 70 mm (5). These films were bonded together in the arrangement shown in Figure 2, with their respective vertical and horizontal directions parallel, and a 1 mm gap between the horizontal edges of adhesive film (I) and adhesive film (II), with the adhesive layer of each film facing the release liner. Before bonding, the release liners on each adhesive film were removed. Next, the protective film obtained in manufacturing example 11 was cut to a size of 150 mm in length and 70 mm in width, and was attached to the base material layer side of each adhesive film so that it overlapped the release liner when viewed from the planar direction. As a result, a reinforcing film (1) is obtained in which two adhesive films (2) and (5) are arranged with a gap between them and one release liner and one protective film. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0282] [Examples 2-12] Reinforcement films (2) to (12) were obtained in the same manner as in Example 1, except that the types of adhesive film used as adhesive film (I) and adhesive film used as adhesive film (II) were changed as shown in Table 2. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0283] [Comparative Examples 1-12] Reinforcement films (C1) to (C12) were obtained in the same manner as in Example 1, except that the types of adhesive film used as adhesive film (I) and adhesive film used as adhesive film (II) were changed as shown in Table 2. The results are shown in Table 2. Furthermore, Table 3 shows the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (I), and the peeling force (A) of the release liner and the peeling force (B) of the protective film in the area of adhesive film (II).
[0284] [Table 2]
[0285] [Table 3] [Industrial applicability]
[0286] The reinforcing film according to the embodiment of the present invention can be suitably used, for example, for reinforcing optical components. The reinforcing film according to the embodiment of the present invention can be particularly suitably used in devices in which a camera is mounted below the display. [Explanation of Symbols]
[0287] 1000 Reinforcement Film 100 Peel-off Liners 200 protective films 300a adhesive film 300b Adhesive Film 300c adhesive film 10a Base material layer 10b Base material layer 20a Adhesive layer 20b Adhesive layer
Claims
1. A reinforcing film in which two or more PSA films are arranged with a gap between one release liner and one protective film, Each of the two or more adhesive films includes a base layer and an adhesive layer, the pressure-sensitive adhesive layers of the two or more pressure-sensitive adhesive films are directly laminated to the one release liner; The two or more adhesive films include at least one adhesive film (I) and at least one adhesive film (II); The pressure-sensitive adhesive film (I) has a retardation of 0 nm to 10 nm or 6000 nm or more, The adhesive film (II) has a length of less than 1.5 mm on the long side of each of the air bubbles and the deformed portion of the substrate when a small piece cut into a size of 10 mm x 50 mm is thermocompressed at 170°C for 10 seconds under a load of 2 kg. Reinforcement film.
2. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive film (I) has a storage modulus at 170° C. of 5.0×10 3 Pa or more 5.0×10 5 The reinforced film of claim 1 , wherein the elastic modulus is less than 100 Pa.
3. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive film (II) has a storage modulus at 170° C. of 5.0×10 3 Pa or more 5.0×10 5 The reinforced film according to claim 1 or 2, wherein the elastic modulus is less than Pa.
4. The reinforcing film according to claim 1 , wherein the area of the adhesive film (I) is larger than the area of the adhesive film (II).
5. The reinforcing film according to claim 1 , which is a reinforcing film for optical members.
